The Eclecticism of Ahmad Dahlan's Ideas at Muhammadiyah Universities - Ani Aryati; Eka Yanuarti (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study examines Ahmad Dahlan's educational philosophy and its application at Muhammadiyah University of Palembang (UMP). Dahlan emphasized Islamic education as a means to enhance societal welfare and align with human needs. A qualitative approach was employed, incorporating phenomenology to explore subjective experiences of study participants. Primary data was gathered through participant observation and in-depth interviews, while secondary data was derived from institutional documents and literature on Dahlan's educational philosophy. Findings reveal that Dahlan’s educational principles, while foundational, remain unsystematized. He advocated for Islamic education grounded in practical life improvement, aligning with people's needs. At UMP, implementation of Dahlan’s philosophy is partial. Shifts have occurred, notably in the principles of education, which now align more with national education system laws than solely the Quran and Hadith. Additionally, leadership at UMP shows limited integration of Dahlan’s ideas, often exhibiting elitism that diminishes organizational inclusivity and support for marginalized communities. The study highlights gaps between Dahlan’s foundational principles and their practical application at UMP. Leadership challenges and adherence to broader educational frameworks contribute to these discrepancies. While Ahmad Dahlan's educational philosophy offers essential principles for Islamic education, UMP has yet to fully realize its potential. Addressing leadership and systemic alignment issues is critical to enhancing the institution's adherence to Dahlan’s vision.